Measurement of the CP asymmetry in B−→D-sD0 and B−→D−D0 decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; Kolpin, Michael; et al. (Journal of high energy physics, 2018)
The CP asymmetry in B− → D s − D0 and B− → D−D0 decays is measured using LHCb data corresponding to an integrated luminosity of 3.0 fb−1, collected in pp collisions at centre-of-mass energies of 7 and 8 TeV. The results are ACP(B−→D−sD0)=(−0.4±0.5±0.5)%andACP(B−→D−D0)=(2.3±2.7±0.4)%ACP(B−→Ds−D0)=(−0.4±0.5±0.5)%andACP(B−→D−D0)=(2.3±2.7±0.4)% {\mathcal{A}}^{CP}\left(B^{-}→ D_s^{-}{D}^0\right)=\left(-0.4± 0.5± 0.5\right)%\kern0.5em and\kern0.5em {\mathcal{A}}^{CP}\left(B^{-}→ D^{-}{D}^0\right)=\left(2.3± 2.7± 0.4\right)% , where the first uncertainties are statistical and the second systematic. This is the first measurement of ACP(B−→D−sD0)ACP(B−→Ds−D0) {\mathcal{A}}^{CP}\left(B^{-}→ D_s^{-}{D}^0\right) and the most precise determination of ACP(B−→D−D0)ACP(B−→D−D0) {\mathcal{A}}^{CP}\left(B^{-}→ D^{-}{D}^0\right) . Neither result shows evidence of CP violation. Open image in new window